Determination of crude protein and crude fat content in Japanese quail (Coturnix coturnixjaponica) Fed with Black soldier fly larvae - Rodiah Hamidi (2016)
This thesis outlines a research conducted to investigate the effect of feeding Japanese quails with black soldier fly larvae (BSFL) in terms of their crude protein and crude fat content. Basically in previous studies, the larvae had been used in several aspects such as in composting, aquaculture, manure management and others. ln order to conduct the research, 45 Japanese quails at the age of 2 weeks were fed with the larvae in different percentages. Three treatments and three replications are applied which is treatment 1 that serves as a control group (100% commercial feed), treatment 2 with 20% of BSFL and 80% commercial feed, and treatment 3 with 25% BSFL and 75% commercial feed. A proximate analysis was used in determining the crude protein and crude fat content of the quail meat where Kjehdahl method was used for protein estimation while Soxtec extraction method was used for fat estimation. The results shows that the highest protein content was contributed by treatment 2, 78.0018 and followed by treatment 3 (77.3306) and treatment 1 (76.4952). While the lowest fat content was spotted in treatment 3 with 12.7868 and followed by treatment 2 (13.2757) and treatment 1(17.9772).